Socialization of the Characteristics of the Arabic Language during the Pre-Islamic (Jahiliyyah) Period as an Effort to Strengthen Islamic Linguistic Insight - Maswan Ahmadi; Andi Abdul Hamzah; Kamaluddin Abu Nawas (Yayasan Rahmat Islamiyah, 2026)
This Community Service Program (PKM) aimed to enhance public literacy on the characteristics of the Arabic language during the Jahiliyah (Pre-Islamic) period as a foundation for understanding the development of Arabic and the Qur'an. The program was implemented through educational sessions, lectures, interactive discussions, and question-and-answer activities involving community participants. The materials covered the socio-cultural background of pre-Islamic Arab society, the characteristics of the Arabic language during the Jahiliyah period, the traditions of Jahiliyah poetry and literature, the moral values embedded in these literary works, and their relevance to contemporary Arabic language learning and Islamic education. The results of the program demonstrated an improvement in participants' understanding of the development of the Arabic language prior to the revelation of the Qur'an, the significance of Jahiliyah literary traditions as an integral part of the Islamic intellectual heritage, and their contribution to contextual Arabic language learning. Participants also showed a high level of enthusiasm throughout the activities and were able to relate the materials to Arabic language teaching practices in educational settings. In conclusion, this community service program successfully strengthened participants' Islamic literacy and broadened their understanding of the historical development of the Arabic language as a fundamental basis for comprehending the Qur'an and Islamic sciences.